IMPLEMENTATION OF DISTRIBUTION OF INHERITANCE IN PATRILINEAL SOCIETY: (A STUDY IN METINARO SUB-DISTRICT, DILI MUNICIPALITY, TIMOR-LESTE) - Anastacio Mendonça; Moh. Muhibbin; Rahmatul Hidayati (Pena Cendekia Insani, 2025)
This research focuses on the dynamics of the patrilineal-based customary inheritance system in the Metinaro Sub-District, Dili Municipality, by examining how these inheritance practices shape social structures, reinforce patriarchal dominance, and create gender inequality. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and a literature review of customary and academic sources. The results show that the inheritance system in Metinaro not only transfers physical assets such as land and traditional houses to sons, but also bequeaths socio-spiritual responsibilities recognized through customary rites and the legitimacy of traditional figures. In contrast, women experience structural subordination, with limited access to family assets and merely symbolic involvement in the inheritance process. However, initiatives for change are beginning to emerge among the younger generation, proposing a more inclusive inheritance model, influenced by education, national law Law Number 10 of 2011/Timor-Leste's civil code in article 1888 (Ideas) Succession refers to one or more people who legally own the inheritance of a deceased person to be distributed to others. And modern values. The implications of this research indicate the importance of intergenerational dialogue and the active involvement of traditional leaders as agents of cultural transformation to create a more just and contextual inheritance system.